DNA-PAINT MINFLUX nanoscopy - Lynn M. Ostersehlt; Daniel C. Jans; Anna Wittek; Jan Keller‐Findeisen; Kaushik Inamdar; Steffen J. Sahl; Stefan W. Hell; Stefan Jakobs (2022)
Abstract MINimal fluorescence photon FLUXes (MINFLUX) nanoscopy, providing photon-efficient fluorophore localizations, has brought about three-dimensional resolution at nanometer scales. However, by using an intrinsic on–off switching process for single fluorophore separation, initial MINFLUX implementations have been limited to two color channels. Here we show that MINFLUX can be effectively combined with sequentially multiplexed DNA-based labeling (DNA-PAINT), expanding MINFLUX nanoscopy to multiple molecular targets. Our method is exemplified with three-color recordings of mitochondria in human cells.